Joanne, 7 times Dean’s list awarded with Royal Academic Award - UMP, PNC (2018)
Joanne Bong Shan Shan, 24, is the recipient of the Royal Academic Award (Excellence Medal) presented during Universiti Malaysia Pahang (UMP) 13th Convocation Ceremony.